PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS V SD NEGERI 1 SUMBEREJO DENGAN MODEL PROBLEM BASED LEARNING(PBL) DAN MEDIA VIDEO ATAU GAMBAR PADA PEMBELAJARAN PENDIDIKAN PANCASILA - Aghneta Putri Cahyati; Safitri Nur Inwanti; Dwi Anna Hastuti; Susilo Tri Widodo; Nur Indah Wahyuni (STKIP Subang, 2023)
This research was motivated by the lack of concentration of students which resulted in low learning outcomes for class V students at SD Negeri 1 Sumberejo in the Pancasila Education subject. This research aims to create interactive teaching and learning activities to improve student learning outcomes by using problem based learning models and video or image media. The data collection techniques used in this research are the results of interviews, observations, tests and documentation. The results of the research showed that there was an increase in the average student learning evaluation score in cycle I of 70.55 and in cycle II of 86.39. Based on the results of the research that has been conducted it can be concluded that learning using the problem based learning model and video or image media can improve student learning outcomes in Pancasila Education learning.